AS PRÁTICAS DO DESIGN UNIVERSAL PARA A APRENDIZAGEM NA INCLUSÃO DE ESTUDANTES COM TEA: PRÁTICAS DO DESIGN UNIVERSAL PARA A APRENDIZAGEM NA INCLUSÃO DE ESTUDANTES COM TEA (REMUNOM, 2025)
This article is part of an ongoing master's research titled “The Trajectory of Inclusion of Students with Autism Spectrum Disorder (ASD): Experiences in the Transition between Inclusive and Special Classes,” conducted by researcher Patrícia de Siqueira Pinto, under the supervision of Klaus Schlünzen Junior. This article proposes a discussion on Universal Design for Learning (UDL) and its intersections with inclusive pedagogical practices, based on the analysis of three dissertations addressing the topic. The bibliographic review method was used to identify and analyze the main points of convergence among the studies, providing a critical reflection on the challenges and potentialities of applying UDL in inclusive educational contexts aimed at students with Autism Spectrum Disorder (ASD). The research seeks to analyze how UDL can be a fundamental tool in overcoming the barriers faced by these students in educational environments, promoting their active participation and success in learning. The study also aims to explore how flexible and adapted pedagogical practices can effectively respond to the specific needs of students with ASD, fostering more inclusive and meaningful learning, and promoting inclusion in a more effective and sustainable manner, thus providing a more accessible and equitable learning environment for all students.